Active Learning Strategies in Higher Education Biology: A Literature Review of Inquiry-Based Learning, Problem-Based Learning, and Flipped Classroom Approaches - zainul muttaqin; Suroso; Liza Choirun Nisa (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2026)
Biology education in higher education faces significant challenges in fostering conceptual understanding, critical thinking, and scientific inquiry skills among students. Traditional teacher-centered instruction often positions students as passive recipients of information, limiting their engagement in knowledge construction. Consequently, active learning strategies have gained considerable attention as effective approaches to improve the quality of biology education. This review aims to examine the implementation of active learning strategies in higher education biology through three major pedagogical approaches: Inquiry-Based Learning (IBL), Problem-Based Learning (PBL), and the Flipped Classroom model. A literature review methodology was employed to synthesize findings from previous studies concerning the implementation of active learning in biology education. The findings indicate that Inquiry-Based Learning effectively enhances scientific reasoning, investigative skills, and conceptual understanding. Problem-Based Learning promotes critical thinking, collaborative learning, and the application of biological concepts to authentic problems. Meanwhile, the Flipped Classroom model encourages self-directed learning and optimizes classroom interaction through active discussions and problem-solving activities. Integrating these approaches provides a promising framework for developing meaningful, student-centered biology instruction that supports the acquisition of twenty-first-century competencies.